Effects of High-Intensity Interval and Moderate-Intensity Continuous Exercise on Inflammatory, Leptin, IgA, and Lipid Peroxidation Responses in Obese Males - de Souza, Daniel C.; Matos, Victor A. F.; dos Santos, Victor O. A.; Medeiros, Italo F.; Marinho, Cristiane S. R.; Nascimento, Paulo R. P.; Dorneles, Gilson P.; Peres, Alessandra; Müller, Carlos H.; Krause, Maurício; Costa, Eduardo C.; Fayh, Ana P. T. (Frontiers in Physiology, 2018)
Purpose: To compare the effects of a single high-intensity interval exercise session (HIIE) with a moderate-intensity continuous exercise session (MICE) on the inflammatory profile, IgA levels and lipid peroxidation in sedentary obese males. Methods: Ten sedentary obese men (age 28.5 ± 2.7 years; BMI 35.9 ± 4.9 kg/m²; body fat 40.6 ± 2.0%) performed three experimental sessions, on separate days with one week wash-out period between interventions, according to a randomized order: 1) HIIE: 10 x 60 seconds at 90% of the HRmax alternated by 60 seconds of active recovery; 2) MICE: 20 min at 70% of the HRmax; 3) Rest - control. Blood and saliva samples were collected before, immediately after and 60 min after the end of each session in order to analyse serum levels of cytokines, IgA and lipoperoxidation markers. Results: Leptin levels decreased immediately after HIIE (P=0.033) and was different from the MICE (P = 0.025). IFN- levels were reduced immediately after (P = 0.032) and 60 min after HIIE (P = 0.003) compared to baseline, and it also increased IL-4 levels immediately after exercise (P = 0.007) compared to resting values. MICE promoted an increase in IFN- levels immediately after exercise (P = 0.025) and 60 min after exercise (P = 0.004) in relation to baseline. Both exercise conditions increased IL-6 levels up to 60 min after exercise (P < 0.05). The IFN-/IL-4 ratio decreased immediately after (P = 0.002) and 60 min after HIIE (P = 0.005) in relation to pre-exercise. No changes were found for IgA-S and TBARS for any of the conditions. Conclusion: A single HIIE session is able to decrease IFN-/IL-4 ratio, indicating an anti-inflammatory response, without alterations in the function of the mucosal immune system and lipoperoxidation. On the other hand, a brief session of MICE induced changes in the pattern of cytokines associated with increased cellular immune function.